The explanation of social action - Martin, John Levi, 1964- (New York ; Oxford : Oxford University Press, 2011)
This title is a critique of the conventional understanding of methods of explanation in the social sciences. The author argues that any scientific approach to explanation must build on the phenomenological experience of actors.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social action; Sociology; Social sciences -- Philosophy